IMPROVING THE MSME ECONOMY THROUGH TRAINING IN LOGO DESIGN AND PRODUCT PACKAGING - Yuliana Yuliana; Sumarsid Sumarsid; Sri Mulyono; Azizah Azizah; Syech Idrus; Raden Irna Afriani; Rika Kartika (Yayasan Education and Social Center, 2022)
MSME packaging is an important part of attracting sales. But on the other hand, challenges that are not easy to face by MSMEs, there are many problems and obstacles for MSMEs in developing their role in competing and distinguishing products sold from other products. Therefore, it is necessary to carry out Community Service activities to overcome it. PKM activities have been carried out to MSME actors. This training on making packaging and logos uses simple design stages and relatively understands the components. There are six stages that must be done to be able to develop brand identity by creating a packaging and logo, this method stage among others. (1) recognize the characteristics of the product or the profile of one's own business; (2) Collection of information; (3) Design (4) Logo Making; (5) Testing; (6) Implementation. The methods of MSME logo making facilities are (1) providing material on logos (2) conducting product surveys, (3) determining various aspects of logo making, (4) the logo creation process which is carried out by discussing with business owners to produce product logos with product names, (5) making supporting media